PERANCANGAN KONSEP BISNIS BUSANA READY TO WEAR INSPIRASI KEBAYA DENGAN TEKNIK SHIBORI - Wiweka Ari Dewanti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
In the midst of the current situation and technological developments, people are increasingly advanced and fast in accessing things. Ease of access brings a lot of influence in the polemic of people's lives. Cultural degradation is one of the real negative impacts felt by society when technology is more advanced, for example in the world of fashion is the fading interest in using Indonesian fabrics and traditional clothing in their daily activities, and people tend to use western inspired fashion with open clothes and strict, inversely proportional to the norms that exist in Indonesia. This introductory report for the final project takes the concept of creating a business whose products prioritize Indonesian clothing such as the kebaya to provide a forum for people to understand their own culture. The concept of designing this business will take the concept of creative space with digital marketing so that easy access is guaranteed, even though the traditional way of marketing still follows current market demands. The dynamics of clothing that occur in Indonesia provides an overview regarding how traditional clothing must be used as well as possible, the development of this business concept is not only to conventionalize kebaya and other clothing, but to participate in inviting the public to make Indonesian culture, especially in fashion, so that they are in demand again and restore their identity Indonesian self.